2001
DOI: 10.1007/s005860100250
|View full text |Cite
|
Sign up to set email alerts
|

A new MRI technique for imaging scoliosis in the sagittal plane

Abstract: IntroductionIn idiopathic scoliosis, biomechanical, biological and clinical views confirm that the deformity in the sagittal plane is of primary pathogenetic significance [8]. A fixed lordotic section causes rotation and increased lateral curvature of the spine as a result of the asymmetry in the coronal plane [2]. Various studies confirm that lordosis of the thoracic vertebrae is characteristic for idiopathic scoliosis in adolescents [3,8,11].The scoliotic deformity in the follow-up of scoliosis patients is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…28 Many authors have already demonstrated that the TK is smaller for thoracic curves than for control curves. 11,14,29,30 The small TK is related to the disturbed growth of the vertebral body in thoracic AIS. 14 In contrast, Propst-Proctor and Bleck 12 found no significant difference in the TK between patients with scoliosis and control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…28 Many authors have already demonstrated that the TK is smaller for thoracic curves than for control curves. 11,14,29,30 The small TK is related to the disturbed growth of the vertebral body in thoracic AIS. 14 In contrast, Propst-Proctor and Bleck 12 found no significant difference in the TK between patients with scoliosis and control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, alternative non-invasive, radiationfree, and reliable methods to study scoliosis are urgently sought. Magnetic resonance imaging (MRI) could reconstruct high-quality tomographic images of spinal vertebrae [17,18]. However, the use of MRI is costly and time consuming; therefore, its use to evaluate AIS still remains very limited.…”
Section: Introductionmentioning
confidence: 99%
“…the presence of a syrinx or other intraspinal pathologies [2,4]. The department of radiology at the University of Bonn developed the MR total spine imaging to reduce the radiation exposure in the follow-up of scoliosis patients [5,10]. A further reconstruction algorithm allows visualising the whole spine in vertical projections with rotational steps of 2°, from )90°to 90°, referred to as MR animation.…”
mentioning
confidence: 99%